FACTOR STRUCTURE OF TEACHER SELF-ASSESSMENT INSTRUMENT (SITE II) - Stanislava MARIĆ JURIŠIN; Borka MALČIĆ (Universitaria Publishing House, Craiova, 2022)
The purpose of the current study was to test psychometric characteristics of the Self-assessment Instrument for Teacher Evaluation - SITE II (Akram & Zepeda, 2015), namely, to determine the factor structure of the instrument which would enable us to conduct a research of the teacher self-evaluation. The study sampled 310 teachers of upper-primary subjects and elementary school grade teachers from 16 primary, mixed-sex public schools in Serbia. The researchers have applied exploratory factor analysis and extracted variables and determined four factors which correlate moderately and positively, with satisfactory reliability of all four sub-scales. The factors are Subject Matter Knowledge, Instructional Planning and Strategies, Learning Environment and Effective Communication, Assessment. The conclusion is that the SITE II scales in our sample, can in fact be used in its modified version of 26 items and a four-factor structure of the instrument.